Optimizing Anthurium Cultivation: Advancements in Greenhouse Design for Enhanced Plant Quality in Controlled Environments - Albertus Bahri; Chairi Kamoga; Kinza Adiguna Pallawarukka (Vertex, 2023)
Anthuriums, renowned for their captivating blooms and lush foliage, thrive in controlled environments. This research delves into the nuanced intricacies of greenhouse design, aiming to optimize growth conditions and enhance the quality of anthurium plants. Through meticulous experimentation and comparative analysis of various greenhouse configurations, the study explores the impact of structural elements, environmental variables, lighting strategies, and soil management on anthurium growth and flowering patterns. Distinct greenhouse structures, including glass, polycarbonate, and advanced plastics, were scrutinized for their effects on anthurium health and quality. Findings reveal the significance of elements such as insulation, humidity regulation, ventilation, and balanced lighting strategies in fostering superior plant vitality. Polycarbonate or advanced plastic structures emerged as optimal environments, ensuring stable conditions conducive to vibrant foliage, prolific blooms, and overall plant vigor. The research extends beyond plant quality, emphasizing economic viability and sustainability. While aesthetics traditionally favored glass structures, the evidence supporting energy efficiency and reduced maintenance costs of alternative materials underscores their practicality in commercial anthurium cultivation. These insights not only redefine greenhouse design paradigms but also serve as a guiding beacon for future research and industry practices. They pave the way for innovative approaches and sustainable cultivation methods, heralding a new era of precision and excellence in anthurium cultivation within controlled greenhouse environments.